Israel : 2012 Article IV Consultation: Staff Report; Informational Annex; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Israel. (IMF Staff Country Reports; Country Report, 2012)
This 2012 Article IV Consultation reports that Israel has emerged from the 2008-09 global crisis with strong economic growth, a resilient banking system, and unemployment at historic lows. Exports, at 40 percent of GDP, depend on global demand for high-technology products, such as electronics and pharmaceuticals, and communications. One-third of exports go directly to Europe, with more routed there indirectly. Given the country's weak direct trade linkages to the region, regional tensions mainly affect Israel through security, investor and consumer confidence, and public finances.